On the mechanisms of InGaN electron cooler in InGaN/GaN light-emitting diodes - Zhang, Xueliang (2014)
Electron overflow limits the quantum efficiency of InGaN/GaN light-emitting diodes. InGaN electron cooler (EC) can be inserted before growing InGaN/GaN multiple quantum wells (MQWs) to reduce electron overflow. However, detailed mechanisms of how the InGaN EC contributes to the efficiency improvement have remained unclear so far. In this work, we theoretically propose and experimentally demonstrate an electron mean-free-path model, which reveals the InGaN EC reduces the electron mean free path in MQWs, increases the electron capture rate and also reduces the valence band barrier heights of the MQWs, in turn promoting the hole transport into MQWs.